2023
DOI: 10.3390/molecules28248075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sous-Vide on Quality, Structure and Flavor Characteristics of Tilapia Fillets

Luqian Yang,
Zhaoyong Li,
Tianxiang Xie
et al.

Abstract: To investigate the effects of traditional high-temperature cooking and sous-vide cooking on the quality of tilapia fillets, muscle microstructure, texture, lipid oxidation, protein structure, and volatile compounds were analyzed. In comparison with samples subjected to traditional high-temperature cooking, sous-vide-treated samples exhibited less protein denaturation, a secondary structure dominated by α-helices, a stable and compact structure, a significantly higher moisture content, and fewer gaps in muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Karki et al (2023) stated that the TBARS values of tilapia fish cooked with the sous vide technique were within acceptable consumption limits until the end of storage. Yang et al (2023) reported that the TBA value of tilapia fillets processed using the sous-vide method (0.47 ± 0.06 mg MDA/kg) was significantly lower compared to the control group (0.69 ± 0.03 mg MDA/kg) (p<0.05). They observed that the sous-vide cooking method has the capacity to effectively inhibit the lipid oxidation process in meat.…”
Section: Ph Tbars and Tvb-nmentioning
confidence: 96%
“…Karki et al (2023) stated that the TBARS values of tilapia fish cooked with the sous vide technique were within acceptable consumption limits until the end of storage. Yang et al (2023) reported that the TBA value of tilapia fillets processed using the sous-vide method (0.47 ± 0.06 mg MDA/kg) was significantly lower compared to the control group (0.69 ± 0.03 mg MDA/kg) (p<0.05). They observed that the sous-vide cooking method has the capacity to effectively inhibit the lipid oxidation process in meat.…”
Section: Ph Tbars and Tvb-nmentioning
confidence: 96%